Regulating sustainable public procurement in Turkey in the context of the European Union membership - Kaya, Mehmet Bedii (2014)
This thesis examines the regulation of sustainable public procurement in the Republic of Turkey in the context of Turkey’s membership negotiations with the European Union. Sustainable public procurement is the procurement whereby contracting authorities take account of all three pillars of sustainable development (economic, social and environmental) when procuring goods, services or works.